Alteração e concentração ferruginosa no arenito do Membro Serra da Galga (Triângulo Mineiro - MG) - Mariano, Érika [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The origin of ferruginous sediments in the Triângulo Mineiro sedimentary plateau has never been previously studied. This work relates the sandstone of Serra da Galga Member with those ferruginous levels, intending to evaluate the possible formation of a ferruginous layer by lateritic processes. In Brazil, 75% of the surface is covered by lateritic layer, formed from the alteration of rocks in tectonically stable environment with seasonal tropical climate. The Triângulo Mineiro has the characteristics that favor lateritization, therefore, the work is developed from the petrographic analysis of a weathering profile of Serra da Galga Member, examining the change of the sandstones primary minerals and its evolution through the weathering. The observations and micromorphological descriptions of parental material and its weathering products provide important information about the newly formed secondary minerals and, when combined with geochemical and mineralogical data, allow us to interpret the relationship of the original material (sandstone) with ferruginous layer. The analysis compares the primary and secondary minerals, structures and textures over weathering profile

A origem de sedimentos ferruginosos na chapada sedimentar do Triângulo Mineiro nunca foi objeto de estudos anteriores. Este trabalho relaciona o arenito do Membro Serra da Galga com estes níveis ferruginosos, pretendendo-se avaliar a possível formação de uma couraça por processos lateríticos. No Brasil, 75% da superfície é coberta por camadas lateríticas, formadas a partir da alteração de rochas em ambiente tectonicamente estável de clima tropical sazonal. O Triângulo Mineiro possui características que favorecem a lateritização, sendo assim, o trabalho se desenvolve a partir da análise petrográfica de um perfil de alteração do Membro Serra da Galga, examinando-se a alteração dos minerais primários do arenito e sua evolução com o decorrer do intemperismo. As observações e descrições micromorfológicas do material parental e de seus produtos de intemperismo fornecem importantes informações sobre os minerais secundários neoformados e, quando associadas com dados geoquímicos e mineralógicos, permitem interpretar a relação do material original (arenito) com a camada ferruginosa. A análise compara minerais primários e secundários, estruturas e texturas ao longo do perfil de alteração
Keywords: Petrologia; Arenito; Sedimentação e depósitos; Sedimentos (Geologia); Solos - Composição; Laterita; Minerais; Triangulo Mineiro (MG)